Domesticating Social Alarm Systems in Nursing Homes: Qualitative Study of Differences in the Perspectives of Assistant Nurses - Fangyuan Chang; Britt Östlund; Sanna Kuoppamäki (JMIR Publications, 2023)
BackgroundNew social alarm solutions are viewed as a promising approach to alleviate the global challenge of an aging population and a shortage of care staff. However, the uptake of social alarm systems in nursing homes has proven both complex and difficult. Current studies have recognized the benefits of involving actors such as assistant nurses in advancing these implementations, but the dynamics by which implementations are created and shaped in their daily practices and relations have received less attention. ObjectiveBased on domestication theory, this paper aims to identify the differences in the perspectives of assistant nurses when integrating a social alarm system into daily practices. MethodsWe interviewed assistant nurses (n=23) working in nursing homes to understand their perceptions and practices during the uptake of social alarm systems. ResultsDuring the four domestication phases, assistant nurses were facing different challenges including (1) system conceptualization; (2) spatial employment of social alarm devices; (3) treatment of unexpected issues; and (4) evaluation of inconsistent competence in technology use. Our findings elaborate on how assistant nurses have distinct goals, focus on different facets, and developed diverse coping strategies to facilitate the system domestication in different phases. ConclusionsOur findings reveal a divide among assistant nurses in terms of domesticating social alarm systems and stress the potential of learning from each other to facilitate the whole process. Further studies could focus on the role of collective practices during different domestication phases to enhance the understanding of technology implementation in the contexts of complex interactions within a group.